Development of Betel Nut Splitting Machine - Muharni, Riza; Kurniawan Arief, Rudi; Fitra, Muhammad; Dwiharzandis, Aggrivina (Universitas Negeri Padang, 2024)
The main purpose of this design is to make betel nut splitting machine to obtain maximum and effective production results and reduce the risk of work accidents. The stages in the manufacture of this betel nut splitting machine consist of literature study, tool drawing design, tool and material preparation, tool making and assembly, then testing and analysis stages. Specifications of betel nut splitting machine with a length of 800 mm, width 600 mm, height 1000 mm. Basically, the process in the introduction rotor and the cleavage by the blade is designed in such a way as to fulfill the cleavage function. This machine could produce up to 160kg of betel nut within one hour.